Etnomatematika di Balik Kerajinan Anyaman Bali - Puspadewi, Kadek Rahayu; Putra, I Gst. Ngurah Nila (Jurnal Matematika; Vol 4 No 2 (2014), 2014)
This paper is study about the existence of ethnomathematics on the Bali woven handicraft. Ethnomathematics is mathematics that grow and develop in a particular culture. Unconsciously, the society use tesselation concepts in making woven handicraft. A tessellation is a special type of pattern that consists of geometric figures that fit without gaps or overlaps to cover the plane. The existence of ethnomathematics on woven handicraft can be used as a source of learning and of course can make learners better understand how their cultural relate with mathematics.
Keywords: ethnomathematics; woven handicraft; tesselation